2010
DOI: 10.1055/s-0029-1243225
|View full text |Cite
|
Sign up to set email alerts
|

Religiosität, Spiritualität, Gesundheit und berufsbezogene Verhaltensmuster bei Pastoren zweier freikirchlich-protestantischer Denominationen

Abstract: The results show distinct psychosocial strain patterns of pastors. Religiosity and spirituality may be an important resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…High DSE's strongly predicted attitude towards and utilization of religion in social work practice, whereas organized religion measures were not predictive [50]. A study of Protestant ministers in Germany showed more DSE's correlated with diminished burnout [51].…”
Section: Dses Work-related Outcomes and Burnoutmentioning
confidence: 88%
“…High DSE's strongly predicted attitude towards and utilization of religion in social work practice, whereas organized religion measures were not predictive [50]. A study of Protestant ministers in Germany showed more DSE's correlated with diminished burnout [51].…”
Section: Dses Work-related Outcomes and Burnoutmentioning
confidence: 88%
“…For example, it was used to study the relations between working behaviors and psychological and psychosomatic symptoms (Bauer et al 2006), to track changes in students' working behavior over time (Voltmer et al 2010b) or to compare behavior and experience patterns of diVerent occupational types (Voltmer et al 2011). Voltmer et al (2010a) studied the working behaviors of pastors from two diVerent evangelical denominations. They found a diVerence between the healthier types G and S and the risk pattern B in the dimensions of daily spiritual experience (e.g., "to sense the presence of god") and positive religious coping (e.g., "to Wnd strength and support in god"), with higher expressions for the healthier types.…”
Section: Assessing Work-related Behavior and Experiencementioning
confidence: 99%
“…As a consequence it is to expect that spiritual life and fulfilment will be affected too either in a positive or negative way. In fact, first findings among protestant pastors show that higher spirituality was related to healthier work-related behaviour patterns [13]. But what about spiritual feelings of those who professionally care for the spiritual side of others, what about chaplains and priests who are suggested to have an active spiritual life?…”
Section: Introductionmentioning
confidence: 99%